PELATIHAN TATA RIAS WAJAH GUNA PENGEMBANGAN DIRI SEBAGAI WANITA KARIER BAGI WARGA PERUMAHAN PURI NIRWANA PANDANWANGI KOTA MALANG - Shinta Maharani Trivena; Rena Feri; Lina Budiarti; Tatiana Kristianingsih; Rizky Kurniawan Murtiyanto (Jurnal Pengabdian kepada Masyarakat, 2020)
This community service aims to provide the residents of Puri Nirwana Pandanwangi Housing with skills, especially women, to be able to apply makeup to support their appearance and career because not all of them can apply makeup well. This training is in collaboration with the Puri Nirwana Pandanwangi Housing Association because the majority of women who are female are career women. Makeup training activities can be used for daily makeup, work, or to attend important events or meetings.Participants take part in this training activity from start to finish even with limited time, and keep their distance during the activity in the context of social restrictions to prevent the Covid 19 virus. The knowledge gained during this training activity is directly applied by the training participants by dressing themselves, and the make-up made by the participants was very satisfying.